Transfers between the Lagrangian points and the primaries considering radiation pressure - Oliveira, Geraldo Magela C.; Gomes, Vivian M. [UNESP]; Prado, Antonio F. Bertachini De A.; Sanchez, Diogo M. (My University, 2016)
The idea of the present paper is to study transfers in the restricted three-body problem considering the effects of the radiation pressure in the trajectory of the spacecraft in a bi-impulsive maneuver. Three systems of primaries are used: Sun-Earth, a generic Sun-asteroid system and a system of asteroids. Transfers among the Lagrangian points and between the Lagrangian points and the primaries are considered. The results show that the radiation pressure has a significant participation in the process, in particular in the system formed by asteroids, because their gravitational forces are smaller compared with the systems having larger bodies. In the case of the asteroid system, it is possible to find solutions with lower fuel consumption by considering the solar radiation pressure. The idea is not to use the radiation pressure as a control, but just to measure its effects when performing the bi-impulsive transfer. It is very important to consider this force or the spacecraft will not reach the desired point.